Initial Experience of Intentional Internal High-Dose Policy Volumetric Modulated Arc Therapy of Neck Lymph Node Metastases ≥ 2 cm in Patients With Head and Neck Squamous Cell Carcinoma - Kashihara, Tairo; Nakamura, Satoshi; Murakami, Naoya; Ito, Kimiteru; Matsumoto, Yoshifumi; Kobayashi, Kenya; Omura, Go; Mori, Taisuke; Honma, Yoshitaka; Kubo, Yuko; Okamoto, Hiroyuki; Takahashi, Kana; et al. (Frontiers in Oncology, 2021)
Background and purpose: Most locoregional recurrences after definitive radiotherapy for head and neck squamous cell carcinoma (HNSCC) develop "in-field." Dose escalation while sparing organs at risk can be a good solution for improving local control without increasing adverse effects. This study investigated the safety and effectiveness of volumetric modulated arc therapy (VMAT) using intentionally internal high-dose policy (IIHDP) to treat neck lymph node metastases (NLNM) ≥ 2 cm in HNSCC patients. Materials and methods: We analyzed 71 NLNM from 51 HNSCC patients who had received definitive radiotherapy to treat NLNM ≥ 2 cm using the VMAT technique in our institution between February 2017 and August 2019. Thirty-seven NLNM from 25 patients were treated using IIHDP VMAT (group A), and 34 NLNM from 27 patients were treated with homogeneous-dose distribution policy (HDDP) VMAT (group B). One patient with three NLNM had one lymph node assigned to group A and the other two to group B. Adverse events and local recurrence-free survival (LRFS) was compared between the two groups. Results: In the median follow-up period of 527 days, there were no significant differences between the groups in terms of dermatitis or mucositis ≥ grade 2/3, but LRFS was significantly longer in group A (p = 0.007). In the Cox regression analysis after adjustment for the propensity score, group A also showed an apparently superior LFRS. Conclusion: Our initial experience of IIHDP VMAT suggested that IIHDP VMAT to treat HNSCC neck lymph node metastases measuring ≥ 2 cm was feasible and possibly led to better local control than HDDP VMAT.